Application of Intra-Class Correlation to Multi-Rater Agreement on Students’ Grading - Adetunji . A. A; Alo N. G.; Anibijuwon A. A. (Darul Yasin Al Sys, 2026)
Fair and credible student assessment depends on consistent grading practices, particularly when multiple raters evaluate academic performance using a shared rubric. This study aimed to examine the consistency of students’ grading by applying the intraclass correlation approach to multi-rater assessments of academic performance. The reliability of ratings was evaluated using the Intraclass Correlation Coefficient (ICC) for continuous rating scores. Data were obtained from records of students’ assessments of project and seminar presentations. The findings revealed varying levels of agreement among raters, indicating that grading practices were generally inconsistent, although some degree of agreement was observed across different assessed variables. These results highlight the importance of applying inter-rater reliability statistics in educational assessment to identify inconsistencies in scoring practices. The study concludes that improving grading fairness and objectivity requires regular rater calibration and the consistent use of standardized rubrics. This study contributes to assessment practice by emphasizing the value of reliability analysis in strengthening the quality and credibility of academic evaluation.